Synovial fluid viscosity with synovial fluid cell count, valuable diagnostic marker of prosthetic joint infections - Samo Roškar; René Mihalič; Anže Mihelič; Rihard Trebše (Scientific Reports)
Abstract In the absence of standard criteria for prosthetic joint infections (PJI), several diagnostic modalities have been proposed mostly concentrating on novel biochemical markers. The physical chemistry markers received scarce attention. Synovial fluid (SF) viscosity could be considered as marker for PJI, however, its diagnostic value of PJI remains unknown. Our study aimed to determine the potential of SF viscosity as a diagnostic marker of PJI and compare it to SF cell count with differential (CCD). We prospectively analysed 123 SF samples (58 septic and 65 aseptic) for viscosity and CCD of SF obtained during hip and knee revision procedures. The diagnosis of PJI based on EBJIS criteria. The viscosity cut-off for PJI was calculated and the diagnostic power was compared to CCD. The mean SF viscosity in the PJI group was 8.5 ± 0.4 mPa s and 103.2 ± 18.8 mPa s in the aseptic group (p < 0.05). SF viscosity achieved 100% sensitivity and 85.3% specificity, with AUC 0.832 (95% CI 0.739, 0.925). Combination of SF viscosity and CCD achieved AUC 0.951 (95% CI 0.919, 0.987). SF viscosity is more sensitive but slightly less specific in diagnosing PJI than SF CCD. Best diagnostic value is achieved combining SF viscosity with CCD in detection of PJI.